[PP.11.17] CARDIOVASCULAR DISEASE RISK FACTORS AMONG MALE YOUTHS IN SOUTHERN SWITZERLAND: A TRANSVERSAL STUDY. (September 2017) - Muggli, F.; Rabufetti, A.; Simonetti, Gd; Bianchetti, Mg; Gallino, A.
Abstract : Objective: Cardiovascular diseases, first cause of death in Switzerland, are frequently attributable to risk factors already present in children and adolescents. The aim of this study was therefore to describe the prevalence of cardiovascular disease risk factors in 18- to 20-year-old males undergoing medical examination to assess fitness for recruitment into the army. Design and method: An exploratory transversal study, approved from the regional ethic commission, was conducted during the recruitment days. The analysis includes measurement of the anthropometric parameters, arterial brachial pressure, central arterial pressure and arterial stiffness (=pulse wave velocity in m/s). Moreover, a structured questionnaire addressing smoking behavior, sedentariness and familial cardiovascular risk factors, as well as blood analysis for determination of glycaemia, lipids and Vitamin D metabolism values was performed. Results: In the period between 1/4/2014–31/12/2016, 1045 voluntary were included in our study. Following cardiovascular risk factors were present in this young male population: tobacco use (N = 449, 43%), body mass index >25.0 Kg/m 2 (N = 274, 26%); Abdominal circumference > 94.0 cm (N = 117, 11%); Arterial pressure = or >140/90 mm Hg (N = 83, 8%); 25-OH-vitamina D3 rate = or <50 nmol/L (N = 201, 19%); total cholesterol = or > 5.2 mmol/L (N = 54, 5%); uricaemia >500 μmol/L (N = 61, 6%); pulse wave velocity >10 m/s (N = 25, 2.5%). Conclusions: The results of this study allow us to analyze the cardiovascular health of young males living in Southern Switzerland. These results clearly show that a high number of young male present at least one cardiovascular risk factor.